When it just won't go away: oral artemisinin monotherapy in Nigeria, threatening lives, threatening progress - ACTwatch Group; Ujuju, C; Anyanti, J; Newton, PN; Ntadom, G (BioMed Central, 2017)
BACKGROUND: Oral artemisinin monotherapy (AMT), an important contributor to multi-drug resistant malaria, has been banned in Nigeria. While oral AMT has scarcely been found for several years now in other malaria-endemic countries, availability has persisted in Nigeria's private sector. In 2015, the ACTwatch project conducted a nationally representative outlet survey. Results from the outlet survey show the extent to which oral AMT prevails in Nigeria's anti-malarial market, and provide key product information to guide strategies for removal. RESULTS: Between August 10th and October 3rd, 2015 a total of 13,480 outlets were screened for availability of anti-malarials and/or malaria blood testing services. Among the 3624 anti-malarial outlets, 33,539 anti-malarial products were audited, of which 1740 were oral AMT products, primarily artesunate (n = 1731). Oral AMT was imported from three different countries (Vietnam, China and India), representing six different manufacturers and 11 different brands. Availability of oral AMT was highest among pharmacies (84.0%) and Patent Propriety Medicine Vendors (drug stores, PPMVs) (38.7%), and rarely found in the public sector (2.0%). Oral AMT consisted of 2.5% of the national anti-malarial market share. Of all oral AMT sold or distributed, 52.3% of the market share comprised of a Vietnamese product, Artesunat®, manufactured by Mekophar Chemical Pharmaceutical Joint Stock Company. A further 35.1% of the market share were products from China, produced by three different manufacturers and 12.5% were from India by one manufacturer, Medrel Pharmaceuticals. Most of the oral AMT was distributed by PPMVs accounting for 82.2% of the oral AMT market share. The median price for a package of artesunate ($1.78) was slightly more expensive than the price of quality-assured (QA) artemether lumefantrine (AL) for an adult ($1.52). The median price for a package of artesunate suspension ($2.54) was three times more expensive than the price of a package of QA AL for a child ($0.76). CONCLUSION: Oral AMT is commonly available in Nigeria's private sector. Cessation of oral AMT registration and enforcement of the oral AMT ban for removal from the private sector are needed in Nigeria. Strategies to effectively halt production and export are needed in Vietnam, China and India.